Crystal structure of {N1,N3-bis[(1-benzyl-1H-1,2,3-triazol-4-yl)methylidene]-2,2-dimethylpropane-1,3-diamine}bis(thiocyanato-κN)iron(II) - Kateryna Znovjyak; Maksym Seredyuk; Sergey O. Malinkin; Sergiu Shova; Lutfullo Soliev (Acta Crystallographica Section E: Crystallographic Communications, 2020)
The unit cell of the title compound, [FeII(NCS)2(C25H28N8)], consists of two charge-neutral complex molecules related by an inversion centre. In the complex molecule, the tetradentate ligand N1,N3-bis[(1-benzyl-1H-1,2,3-triazol-4-yl)methylene]-2,2-dimethylpropane-1,3-diamine coordinates to the FeII ion through the N atoms of the 1,2,3-triazole moieties and aldimine groups. Two thiocyanate anions, coordinating through their N atoms, complete the coordination sphere of the central ion. In the crystal, neighbouring molecules are linked through weak C—H...π, C—H...S and C—H...N interactions into a two-dimensional network extending parallel to (011). The intermolecular contacts were quantified using Hirshfeld surface analysis and two-dimensional fingerprint plots, revealing the relative contributions of the contacts to the crystal packing to be H...H (35.2%), H...C/C...H (26.4%), H...S/S...H (19.3%) and H...N/N...H (13.9%).